2015
DOI: 10.1039/c5fo00481k
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol suppresses lipid accumulation by inhibiting early adipogenesis in 3T3-L1 cells and zebrafish

Abstract: Kaempferol is a flavonoid present in Kaempferia galanga and Opuntia ficus indica var. saboten. Recent studies have suggested that it has anti-oxidant, anti-inflammatory, anti-cancer, and anti-obesity effects. In this study, we focused on the anti-adipogenic effects of kaempferol during adipocyte differentiation. The results showed that kaempferol inhibits lipid accumulation in adipocytes and zebrafish. Oil Red O and Nile Red staining showed that the number of intracellular lipid droplets decreased in adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 45 publications
5
73
0
Order By: Relevance
“…The protocol consisted of a 15-day exposure to the compound on a high-fat diet background, starting at the first feeding period. For example, curcumin [5053], indole-3-carbinol [54], baicalein [55], dieckol [56], ellagic acid [52], kaempferol [51], quercetin [56], seapolynol [57] and silibinin [58], have all been reported to inhibit lipid accumulation in these early, post-embryonic developmental stages, when the adipocyte lineage is just starting to be established [20,27]. In our work, we used the ZOT protocol at later larval developmental stages, when the animals had a well-established WAT [30].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol consisted of a 15-day exposure to the compound on a high-fat diet background, starting at the first feeding period. For example, curcumin [5053], indole-3-carbinol [54], baicalein [55], dieckol [56], ellagic acid [52], kaempferol [51], quercetin [56], seapolynol [57] and silibinin [58], have all been reported to inhibit lipid accumulation in these early, post-embryonic developmental stages, when the adipocyte lineage is just starting to be established [20,27]. In our work, we used the ZOT protocol at later larval developmental stages, when the animals had a well-established WAT [30].…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte dysfunction is strongly associated with the development of obesity. Many studies have shown that Opuntia extracts such as the flavonoid kaempferol or isorhamnetin can suppress lipid accumulation or inhibit adipogenesis through adipogenic-responsible genes downregulation [97, 98]. The use of cellular models allows a better knowledge of the gene regulations and the metabolic pathways in which plant extracts could interfere.…”
Section: Biological and Medical Properties Of Opuntia Spp In Chromentioning
confidence: 99%
“…Microarray analysis revealed that kaemperol decreases expression of adipogenic transcription factors and triglyceride synthesis-related genes and, conversely, increases gene involved in lipolysis [106]. Many transcriptional factors such as C/EBPβ, KLF4, and KLF5 are downregulated by kaempferol treatment, while negative regulators of adipogenesis such as KLF2 and Pref-1 are upregulated during the early adipogenesis [118]. As with many flavonoids, the anti-adipogenic mechanisms of kaempferol are several.…”
Section: Flavonolsmentioning
confidence: 99%
“…In this context, dietary flavonoids have become the subject of increasing scientific interest due to their effects on adipogenesis. The anti-adipogenic effects of flavonoids are mainly via their effect on a number of molecular targets and regulation of several pathways such as induction of apoptosis [123], suppression of key adipogenic transcription factors [94,95,114,144], activation of AMPK [97,129], and Wnt [115,138] pathways, inhibition of clonal expansion [147,153,155], cell-cycle arrest, and modulation of insulin signaling cascade [118], suggesting flavonoids as effective inhibitors of adipogenesis during determination and terminal differentiation stages. Although these data are encouraging, further investigation is essential to gain insight into the molecular mechanisms that connect extranuclear and nuclear mediators of adipogenesis.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%